Teacher’s Experience and Beliefs: Teaching English by Integrating Web-based Learning - Desy Nur Fakhomah; Abdul Asib; Dewi Rochsantiningsih (RIRAI Publisher, 2020)
Recently, the science and technology improvement has contributed to the improvement in language teaching and learning. There are many various technologies that can be used for teaching and learning English. One of them is web-based learning. However, not all the teachers know how to integrate technology in their teaching process. This study wants to delve deeper understanding into how an English teacher’s beliefs and experience towards web-based learning in English teaching learning process. A narrative inquiry study was conducted towards the participant who has used web-based learning for language teaching and learning at a non-formal school. The teacher’s lesson plans and interview were used for collecting the data. The data were coded and analyzed using Thematic Analysis Single Case Study. The result of this study showed that the participant has positive beliefs toward web-based learning for teaching and learning English.